(untitled) (Modern education and development, 2025)
Nursing plays a critical role in healthcare delivery, deeply affecting patient outcomes, satisfaction, and the overall efficiency of medical systems. This review explores nursing’s multifaceted contributions: direct patient care, evidence-based practice, research, public health, and interprofessional collaboration.